2011
DOI: 10.1101/gad.177238.111
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide function of H2B ubiquitylation in promoter and genic regions

Abstract: Nucleosomal organization in and around genes may contribute substantially to transcriptional regulation. The contribution of histone modifications to genome-wide nucleosomal organization has not been systematically evaluated. In the present study, we examine the role of H2BK123 ubiquitylation, a key regulator of several histone modifications, on nucleosomal organization at promoter, genic, and transcription termination regions in Saccharomyces cerevisiae. Using high-resolution MNase chromatin immunoprecipitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
210
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(232 citation statements)
references
References 64 publications
22
210
0
Order By: Relevance
“…Eviction of acetylated nucleosomes ahead of Pol II permits efficient elongation, whereas reassembly of deacetylated nucleosomes behind the elongating polymerase prevents initiation at spurious sites. Consistent with this scenario, mutations in histone chaperones that promote nucleosome assembly/disassembly, or in enzyme complexes that catalyze or erase histone modifications associated with gene bodies (e.g., H3K9/14 and H4 acetylation, H2B ubiquitylation, and H3K36 di-and trimethylation), affect transcriptional consistency in yeast (49,(53)(54)(55).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Eviction of acetylated nucleosomes ahead of Pol II permits efficient elongation, whereas reassembly of deacetylated nucleosomes behind the elongating polymerase prevents initiation at spurious sites. Consistent with this scenario, mutations in histone chaperones that promote nucleosome assembly/disassembly, or in enzyme complexes that catalyze or erase histone modifications associated with gene bodies (e.g., H3K9/14 and H4 acetylation, H2B ubiquitylation, and H3K36 di-and trimethylation), affect transcriptional consistency in yeast (49,(53)(54)(55).…”
Section: Discussionmentioning
confidence: 83%
“…In mammalian cells, TET functions are linked to both types of histone modifications: high levels of 5hmC are present in the gene bodies of expressed genes; 5hmC distribution in gene bodies is strongly correlated with that of H3K36me3 (43,(56)(57)(58)(59)(60); and TET1 coimmunoprecipitates with SIN3A and HDAC1/2 in mouse ES cells (61). (ii) Also in yeast, H2B ubiquitylation has been implicated in nucleosome dynamics (54,55), and a screen for chromatin regulators that altered the variability of reporter expression in yeast showed that H2B ubiquitylation recruited the Set3C HDAC complex, thereby limiting the high rate of Pol II elongation associated with transcriptional bursts (49). Similarly in mammalian cells, TET2 and TET3 have been linked to H2B ubiquitination through their association with the enzyme O-GlcNAc transferase (OGT) (62-64); OGT attaches O-linked N-acetylglucosamine to H2B (63), a modification required for subsequent H2B ubiquitylation (65).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been pointed out that H2Bub1 could be an activator in transcribed regions while having a repressive function in promoters (Batta et al, 2011;Materne et al, 2016), but the underlying molecular mechanisms have not been studied. These preliminary observations raise the possibility that H2Bub1 could be involved in regulating transcription initiation, which might explain why H2Bub1 depletion could have genespecific effects.…”
Section: Introductionmentioning
confidence: 99%
“…Since several papers have emphasized the role of H2Bub1 in modulating nucleosome ar- (Chandrasekharan et al 2009;Batta et al 2011;Fierz et al 2011;Schulze et al 2011), we herein sought to identify correlation patterns between H2Bub1 and nucleosome architecture.…”
Section: H2bub1 Is Highly Enriched At the Exon-intron Boundaries Of Hmentioning
confidence: 99%